Analisis Faktor-faktor yang Memengaruhi Produktivitas Usaha Sawit Swadaya di Kecamatan Sekadau Hilir - Susanti, Susi; Hutajulu, Josua Parulian; Nugraha, Aditya (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
Oil palm is one of the plantation crops used to meet human needs, so every year there is an increase in demand and an increase in land used for oil palm plantations. The purpose of this research is to analyze the factors that influence the productivity of independent oil palm in Sekadau Hilir District. The research method used in this study is a survey method. The variables used are Seedlings, Fertilizers, Pesticides, Labor, and Pruning. This research uses multiple linear regression analysis. The results show that simultaneously, seedlings, fertilizers, pesticides, labor, and pruning affect the productivity of independent oil palm businesses. This is based on the simultaneous test which shows the calculated F value of 73.810 > F table (2.443) with a significance value of 0.000 < α (0.05). Partially, fertilizer and labor factors influence the productivity of independent oil palm businesses, with respective significance values of 0.00 < α (0.05) for fertilizer and 0.034 < α (0.05) for labor.